Medical-legal aspects of the fungal infection drug therapy in neonatology: evidence-based medicine and off-label prescribing - Marta Ciuffi; Francesco Paribello; Roberto Demontis; Ernesto d'Aloja; Roberta Massa (Hygeia Press di Corridori Marinella, 2014)
The aim of this paper is to focus on the well-known issue of the clinical use of off-label drug therapy in neonatology with respect to evidence-based medicine, with particular reference to antifungal products, in comparison with the wider use in pediatric and adult population. Then we considered the new regulatory approaches carried out in the past decade by the FDA (Food and Drug Administration) and the EMA (European Medicine Agency), aimed to improve newborn and children population inclusion into scientific trials and to promote drug labeling with respect to pediatric indications, and the goals nowadays achieved through the American Pediatric Research Equity Act / Best Pharmaceuticals for Children Act and the European Pediatric Investigation Plans. Finally we pointed out, on the basis of the Italian regulatory framework, the Italian medical-legal liability profiles related to the use of off-label therapies in neonatology. Further efforts are required in the international context to carry forward the process started while in the particular Italian scenario it is to be hoped that a general change of mind towards the off-label drug use in neonatology clinical practice may take place.